Prevalence and Determinants of Tobacco Smoking Among Low-Income Urban Adolescents - Mallol-Villablanca, E (Mary Ann Liebert Inc., 2021)
Background: Tobacco-smoking in children is one of the most crucial public health concerns, which could be highly prevalent in underprivileged populations. Methods: A cross sectional, random sampling survey was conducted to determine the prevalence of current tobacco-smoking and related risk factors among adolescents living in a low-income area of Santiago de Chile. Results: Of the 2,747 adolescents participating in the study, 24.0% [95% confidence interval (CI) 22.3-25.5] were current smokers, with no significant difference between girls and boys. Factors associated with current smoking were as follows: positive attitude to smoking cigarettes offered by peers [odds ratio (OR) 8.0; 95% CI 5.7-11.3, P < 0.001], having smoking best friends (OR 4.0; 95% CI 2.6-6.0, P < 0.001), and passive smoking in the house (OR 1.9; 95% CI 1.2-3.1, P = 0.008). A total of 16.8% (95% CI 11.4-18.2) of children had smoked an entire cigarette at the age of ≤12, and 62.3% (95% CI, 60.5-64.1) were passive smokers at home. Regarding nonsmoking children, 52.4% (95% CI 49.74-55.06) were exposed to tobacco smoke at home. Conclusion: The prevalence of current tobacco-smoking in adolescents is high and increasing compared to previous studies undertaken in the selected low-resourced area. Two-thirds of children who started smoking before the age of 12 years were current smokers at the time of the survey, highlighting the prevalence of the powerful addiction generated and the need for better preventive strategies against tobacco-smoking for children living in low-resource communities. © Copyright 2021, Mary Ann Liebert, Inc., publishers 2021.